Constraints to the Provision of Library and Information Services for the Actualization of Sustainable Development Goals in Open and Distance Learning Centres: Strategies for Intervention - Ekwueme, Loveth Ogoegbunam; Elem, Grace Ndukwe; Chime , Augustina Chinyere (Communicate: Journal of Library and Information Science, 2023)
The failure to achieve the Millennium eight sustainable goals among the members of United Nation gave rise to the United Nations 2030 Agenda with seventeen goals Sustainable Development Goals (SDGs). The study investigated the constraints to the provision of library and information services for the actualization of sustainable development goals in open and distance learning: Strategies for Interventions. A descriptive survey design was adopted for the study. The population of the study comprises all the 62 librarians in National Open University of Nigeria (NOUN). An online questionnaire was used for data collection. Data collected were analysed using descriptive statistics. The results showed the implication of SDGs in open and distance learning included the promotion of education for all, incorporating distance learning mode in conventional education system, training of more teachers and librarians. Also, the findings revealed that the constraints encountered by librarians in the provision of library and information services for the actualisation of SDGs to distance learners in NOUN include high cost of subscription fees for databases, high exchange rate; poor welfare for library personnel, epileptic power supply and poor internet access. The result also identified the strategies to be employed for actualisation of SDGs through library and information services provision as acquisition of information resources that reflects the content of SDGs and promotion of content of SDGs to library users using web format, posters, and giveaways to create awareness on the available resources and services aiming that achieving the SDGs. Keywords: , , ,